2020
DOI: 10.1021/acsaem.0c00354
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Well-Aligned Channels Derived from Wood as a Convection-Enhanced Electrode for Aqueous Flow Batteries

Abstract: Nature has provided scientists and engineers with tremendous inspirations and resources to design new materials, architectures, and devices. Inspired by the transportation of water and ions in trees, a natural freestanding wood carbon (WC) electrode with vertically well-aligned channels and pit pores on the channel walls was adopted as a convection-enhanced electrode for aqueous vanadium redox flow batteries (VRFBs). In addition, carboxylic groups were introduced on WC via nitric acid treatment (A-WC) to impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 44 publications
0
20
0
1
Order By: Relevance
“…In summary, 0D sphere carbonous materials improve active materials' contact and electron transportation in the electrode. Moreover, the sphere structures, such as core-shell and yolk-shell structures, enable blocking or minimizing the active materials' loss caused by phase Bifunctional and tunable mesoporous carbon sphere for Li-sulfur battery [33] Nanostructured Si/porous carbon spherical composite as an anode for Li-ion battery [34] Sandwich-like hollow sphere anode for Li-ion battery [35] 1D carbon fiber • Low percolation threshold • Excellent electrical conductivity Carbon fiber prepared by electrospinning as an anode for Li-ion battery [36] Sulfur@carbonized mesoporous wood fiber as cathode [37] Exfoliated graphite fiber for electrode in flow battery [38] Carbon nanofiber foam pyrolyzing bacterial cellulose [39] 2D layered carbon Stacked graphene used as an anode for Li-ion battery [40] Corrugated graphene sheets as electrodes in a supercapacitor [41] LiNi 0.5 Mn 0.5 O 4 /graphene composites as cathodes for lithium-ion batteries [42] Caterpillar-like and reconfigurable graphene as a sulfur host in Li-sulfur battery [43] 3D bulky carbon • Ordered and interconnected porous structures • Free-standing strucrure • Good electrical conductivity Activated wood carbon and MnO 2 /wood carbon in an asymmetric supercapacitor [44] Freestanding wood-based carbon electrode for vanadium flow battery [45] Wood-derived carbon with a hierarchical porous structure as a gas diffusion layer in Li-O 2 battery [46] F I G U R E 2 (See caption on next page) change, volume expansion, shuttle effect, or pulverization. The excellent electrical conductivity and protection of active materials significantly improve the reversible capacity, rate performance, and cycling stability.…”
Section: Sphere-like Carbonmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, 0D sphere carbonous materials improve active materials' contact and electron transportation in the electrode. Moreover, the sphere structures, such as core-shell and yolk-shell structures, enable blocking or minimizing the active materials' loss caused by phase Bifunctional and tunable mesoporous carbon sphere for Li-sulfur battery [33] Nanostructured Si/porous carbon spherical composite as an anode for Li-ion battery [34] Sandwich-like hollow sphere anode for Li-ion battery [35] 1D carbon fiber • Low percolation threshold • Excellent electrical conductivity Carbon fiber prepared by electrospinning as an anode for Li-ion battery [36] Sulfur@carbonized mesoporous wood fiber as cathode [37] Exfoliated graphite fiber for electrode in flow battery [38] Carbon nanofiber foam pyrolyzing bacterial cellulose [39] 2D layered carbon Stacked graphene used as an anode for Li-ion battery [40] Corrugated graphene sheets as electrodes in a supercapacitor [41] LiNi 0.5 Mn 0.5 O 4 /graphene composites as cathodes for lithium-ion batteries [42] Caterpillar-like and reconfigurable graphene as a sulfur host in Li-sulfur battery [43] 3D bulky carbon • Ordered and interconnected porous structures • Free-standing strucrure • Good electrical conductivity Activated wood carbon and MnO 2 /wood carbon in an asymmetric supercapacitor [44] Freestanding wood-based carbon electrode for vanadium flow battery [45] Wood-derived carbon with a hierarchical porous structure as a gas diffusion layer in Li-O 2 battery [46] F I G U R E 2 (See caption on next page) change, volume expansion, shuttle effect, or pulverization. The excellent electrical conductivity and protection of active materials significantly improve the reversible capacity, rate performance, and cycling stability.…”
Section: Sphere-like Carbonmentioning
confidence: 99%
“…Moreover, owing to ordered hierarchical porous structures, woodbased carbon can provide fluent electrolyte transport channels and sufficient electrochemical reaction sites for flow batteries. Yang et al 45 reported an advanced freestanding wood-based carbon electrode for VFB (see Figure 8D). 97 The electrolyte wettability and specific surface area of the wood carbon electrode were significantly improved after nitric acid treatment, which further promoted electrolyte flowthrough and electrochemical reactions.…”
Section: Bulky Carbonmentioning
confidence: 99%
“…The wood-derived carbon structure is particularly favorable for redox flow batteries. [161][162][163] Jiao et al produced a holey 3D wood electrode by a simple perforation and carbonization process. [161] The holes drilled into the wood enabled diffusion of the electrolyte between the aligned channels, accelerated ion exchange in the electrode, and reduced the concentration polarization in a vanadium flow battery, which had high Coulombic, voltage, and energy efficiencies at current densities between 10 and 40 mA cm −2 .…”
Section: Other Batteriesmentioning
confidence: 99%
“…Similarly, Yang and coworkers improved the flow over the electrode by chemically modifying the wood‐derived carbon. [ 96 ] Carboxylic acid (–COOH) groups were introduced onto pore surfaces by simple nitric acid treatment, leading to a dramatic increase of wettability of wood derived carbon, were the electrolyte was instantaneously adsorbed by the structure. As a result, an enhanced aqueous electrolyte flow within the electrode was achieved, resulting in higher conductivity and associated enhanced electrochemical performance.…”
Section: Wood As Ionic/electronic Conductive Frameworkmentioning
confidence: 99%
“…Special mention deserves the electrochemical performance of wood derived self‐standing 3D carbon in a wide variety of application, such as carbon anodes, current collectors, ORR/OER catalysts for MABs or electrodes in redox flow batteries. [ 79,85,93,94,96,116,125,137 ] This reflects the excellent properties of wood derived materials and their potential to bring the electrochemical energy storage a step closer to sustainable economy. Controlled redox processes : the aligned and oriented channels allow a guided distribution of electrons and ions throughout wood structure, improving the homogeneity of the redox reactions along the surface of the electrodes which in turn enhances the electrode/electrolyte interface interaction and enlarges cell lifespan as well as power density of the cell. A representative example of the ability of wood derived materials in the control of redox processes is presented by Ji and coworkers with a controlled activity towards sodium combining high cyclability at high current densities (5000 cycles at 5 A g –1 ).…”
Section: Outlook and Future Perspectivementioning
confidence: 99%